واقع تطبيق استراتيجية العصف الذهني من طرف أساتذة التربية البدنية والرياضية في الطور الثانوي - بده مسعود; بكاي اسماعيل; عايدي مراد (University of Eloued جامعة الوادي, 2024)
تهدف الدراسة إلى معرفة واقع تطبيق استراتيجية العصف الذهني من طرف أساتذة التربية البدنية الرياضية في الطور الثانوي لبلدية ورقلة، ولتحقيق هذا الهدف قمنا بإجراء دراسة ميدانية على مستوى ثانويات بلدية ورقلة والباغ عددها 13 ثانوية، ولتحقيق هدف الدراسة تم استخدم المنهج الوصفي الذي يناسب طبيعة الدراسة، كما تم الاعتماد على مقياس استراتيجية العصف الذهني لجمع المعلومات، وقد تم توجيهه إلى عينة الدراسة والمكونة من 26 أستاذ التربية البدنية والرياضية في الطور الثانوي، والتي اختيرت بطريقة عشوائية من أصل مجتمع قوامه 34 أستاذ ، كما قمنا بمعالجة وتحليل البيانات المتحصل عليها باستخدام برنامج الإحصاء ، وفي الأخير خلصت الدراسة إلى أن مستوى تطبيق أساتذة التربية البدنية والرياضية للطور الثانوي لاستراتيجية العصف الذهني عال، كما توصلت الدراسة إلى أن الخبرة المهنية ليس لها تأثير بالنسبة لمستوى التطبيق، بالمقابل المستوى التعليمي كان له دور في تطبيق هذه الإستراتيجية لصالح حاملي شهادة الليسانس والماستر على حساب حاملي شهاد دكتوراة.Abstract: This study aims at knowing the reality of applying brainstorming strategy by physical education teachers in the secondary schools of the municipality of Ouargla. To achieve this objective, we conducted a practical study for 13 secondary schools of the municipality of Ouargla. The questionnaire depends also on the brainstorming as a source of information, and it was directed to a sample of the study, which consisted of 26 teachers of physical education and sports in the secondary stage, which were randomly selected out of a community of 34 teachers. The study concluded that the level of applying brainstorming strategy by the teachers of physical and sports education to the secondary stage is higher, and the study also concluded that the professional experience has no effect on the level of the application, in contrast the educational level had a role in the application of this strategy for the benefit of the holders of Bachelor's and Master's degrees at the expense of Ph.D.
Keywords: استراتيجية العصف الذهني; أستاذ التربية البدنية; Brainstorming strategy; teachers of physical education